Length-Weight Relationship and Reproduction of Spotcheek emperor Lethrinus rubrioperculatus Sato, 1978 at Napo Nain Likupang North Sulawesi - Laura, Azhar; Kambey, Alex D.; Bataragoa, M.Sc, Dr. Ir. Nego E.; Pratasik, Silvester B.; Lohoo, Anneke V.; Kusen, Janny D. (Jurnal Ilmiah Platax, 2023)
Spotcheek emperor L. rubrioperculatus lives in association with coral reefs, at a depth of 10-168 m. This species lives on sandy bottoms and along the outer reef slopes. The lemur fish L.rubriopercelatus is a protogynous hermaphrodite fish, there is a sex change from the female phase to the male phase. Research related to sea urchins in Likupang waters has never been carried out, even in general it is very limited in Indonesia. This study aims to analyze the length-weight relationship and reproductive aspects of spotcheek emperor at Napo Nain Likupang waters. Length-weight relationships are growth patterns and condition factors. Reproductive aspects are the level of gonadal maturity, gonadal maturity index, and fecundity. Fish samples were caught using two types of hand lines, hook number 10 with monofilament line number 90 and hook number 12 with monofilament line number 100. Sampling was carried out three times in May, June, and July 2022. The total samples were 80 individuals. consisting of 44 male individuals with a fork length range of 14.7-22.7 cm, 42 female individuals with a fork length range of 13.0-24.0 cm, and 2 individuals of transitional elephant fish, respectively 19.5 and 20.0 cm. Male length-weight relationship W= 0.2332L2.1642 (R2=0.7881) negative allometric growth pattern. Females W = 0.0868L2.505 (R2=0.9575) negative allometric growth pattern. The condition factor for male fish is 1.03 ± 0.22 and 0.99 ± 0.12 for females. The gonadal maturity was found in May for both males and females. Gonad Maturity Index for males ranged from 0.03-0.18 and for females 0.02-1.49. Fecundity ranged from 21.035-3.9497 with an average of 31.530 ± 5.929. The relationship between fecundity and length F=3152L0.7721 (R2=0.24340) Keywords: Growth pattern, Allometric, Gonad, Fecundity. Abstrak Ikan lencam L. rubrioperculatus hidup berasosiasi dengan terumbu karang, pada kedalaman 10-168 m. Spesies ini hidup di dasar berpasir dan di sepanjang lereng terumbu bagian luar. Ikan lencam L.rubriopercelatus adalah ikan hermaprodit protogini, terjadi perubahan kelamin dari fase betina ke fase jantan. Penelitian berkaitan ikan lencam di perairan Likupang belum pernah dilakukan, bahkan secara umum di Indonesia sangat terbatas. Penelitian ini bertujuan untuk menganalisis hubungan panjang-berat dan aspek reproduksi. Hubungan Panjang- berat meliputi pola pertumbuhan dan faktor kondisi di parairan Napo Nain Perairan Likupang. Aspek reproduksi meliputi tingkat kematangan gonad, indeks kematangan gonad dan fekunditas. Sampel ikan ditangkap dengan menggunakan dua jenis pancing ulur (hand line) mata pancing nomor 10 dengan tali monofilament nomor 90 dan mata pancing nomor 12 dengan tali monofilament nomor 100. Sampling dilakukan tiga kali pada bulan Mei, Juni dan Juli 2022. Jumlah sampel 80 individu terdiri atas terdiri dari 44 individu jantan dengan kisaran panjang garpu 14,7-22,7 cm, 42 individu betina dengan kisaran panjang garpu 13,0-24,0 cm, 2 individu ikan lencam transisi kelamin masing 19,5 dan 20,0 cm. Hubungan panjang-berat jantan W= 0,2332L2,1642 (R2=0,7881)pola pertumbuhan alometrik negatif. Betina W = 0,0868L2,505 (R2=0,9575) pola pertumbuhan alometrik negatif. Faktor kondisi jantan bernilai 1,03 ± 0,22 dan 0,99 ± 0,12 ikan betina. Tingkat kematangan gonad ikan yang siap memijah (TKG IV) ditemukan pad bulan Mei baik jantan maupun betina. Indeks Kematangan Gonad jantan berkisar antara 0,03-0,18 dan betina 0,02-1,49. Fekunditas berkisar antara 21.035-3.9497 dengan rata-rata 31.530 ± 5.929. Hubungan fekunditas dengan panjang F=3152L0,7721 (R2=0,24340) Kata kunci : Pola pertumbuhan, Allometrik, Gonad, Fekunditas